The FTAA and the political economy of protection in Brazil and the US - de Paiva Abreu, Marcelo (IDB-INTAL Buenos AiresAR, 2006)
Focuses on reciprocity in the context of regional trade negotiations and on the political economy aspects of the reciprocal trade concessions between the United States and MERCOSUR, which are likely to be required in the transition period towards FTAA